OPTICAL ABSORPTION IN SEMICONDUCTOR NANOWIRE MEDIATED BY ELECTRON-POLAR OPTICAL PHONON AND SPIN-ORBIT INTERACTIONS - Ghukasyan, Tigran K. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2022)
The intrasubband and intersubband absorption of light by free charge carriers in a semiconductor nanowire upon scattering by polar optical phonons mediated by Rashba and Dresselhaus spin-orbit interactions has been studied. The dependence of the absorption coefficient on the energy of the incident photon is investigated by counting the transitions between different conduction subbands. It is shown that the spin-orbit interaction leads to an increase in the coefficient of intrasubband and intersubband absorption of light, with the peaks of the absorption coefficient being determined by the energies of the absorbed photon and the absorbed or emitted phonon. In this case, the difference between the values of the absorption coefficients with or without spin-orbit interaction has maximum in the range of the local minimum of the absorption coefficient obtained by ignoring the spin-orbit coupling.